Challenges of Spreading the Culture of Peace in Iraq from the point of view of Leaders and Intellectuals Elites (Journal of the College of Education for Women, 2023)
The research problem lies in identifying the challenges facing spreading the culture of peace in Iraq, and the most important factors of its instability from the point of view of leaders and intellectual elites.The research derives its importance from the fact that the peace imposed by justice leads to a stable Iraq and a prosperous future.The study aims to identify the most prominent challenges and obstacles created by wars and faced the process of spreading the culture of peace and instability in Iraq, and to shed light on the reasons leading to the employment of the capabilities of community leaders in spreading the culture of peace.The objective of the current research is to identify the challenges of spreading the culture of peace in Iraq, the point of view of the leaders and intellectual elites, the statement of the conceptual framework for the culture of peace, the factors facing the culture of peace, the study was presented.